Tappra martyrer och katolska bråkmakare. Om några historiskt betingade traditioner i den svenska bilden av Polen - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2009)
The article puts together and describes four main traditions of the Swedish perception of the Polish, which have been formed through the centuries by the conflicts and encounters, as well as similarities and differences in the development of societies in these two countries. The historically qualified notions about the Polish as courageous warriors, innocent martyrs, anarchy rioters and catholic fanatics reappear also in Swedish press articles that were published after 1989, sometimes gaining a new meaning. These notions should be interpreted in the background of national narratives of the Swedes since images of the others are being often used while defining one’s own group and consequently they should be seen as a substantial constituent of national identity.